2017
DOI: 10.1002/cad.20189
|View full text |Cite
|
Sign up to set email alerts
|

Improving Early Grade Reading Outcomes:Aprender a Lerin Mozambique

Abstract: The Government of Mozambique has long struggled to improve the low reading levels of children in early grades. With funding from the U.S. Agency for International Development (USAID) in 2012, World Education collaborated with the Ministry of Education and Human Development (MINEDH) to improve reading by developing a research-based reading intervention and testing it in two provinces. This article examines student reading performance from cohorts of second and third graders before and after a 1-year interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Similarly, Ajoke (2017) argued that children's academic outcomes improve when instructional materials are appropriately utilised. Several studies in sub‐Saharan Africa have shown the importance of materials provision for literacy development (Piper et al, 2014; Omuna et al, 2016; Burchfield et al, 2017; Piper et al, 2018).…”
Section: Background and Contextmentioning
confidence: 99%
“…Similarly, Ajoke (2017) argued that children's academic outcomes improve when instructional materials are appropriately utilised. Several studies in sub‐Saharan Africa have shown the importance of materials provision for literacy development (Piper et al, 2014; Omuna et al, 2016; Burchfield et al, 2017; Piper et al, 2018).…”
Section: Background and Contextmentioning
confidence: 99%
“…Similarly, in a more recent Early Grade Reading Assessment (EGRA), the majority of grade 2 and 3 students assessed in 180 randomly selected primary schools lacked foundational literacy skills; students struggled with letter recognition, word reading, reading fluency and comprehension (Raupp et al, ). Poor reading outcomes have been explained by several factors – insufficient instructional hours for literacy classes, poor student and teacher attendance, weak instructional support for bilingual education and limited materials, especially in local languages (Burchfield et al, ; Chimbutane and Benson, ). Arguably, outdated teacher instruction and scarcity of training opportunities were the greatest constraints (MMoE, ; Raupp et al, ).…”
Section: Background and Contextmentioning
confidence: 99%